Association of adolescent dimensional borderline personality pathology with past and current nonsuicidal self-injury and lifetime suicidal behavior: a clinical multicenter study - Kaess, Michael; Brunner, Romuald; Parzer, Peter; Edanackaparampil, Manju; Schmidt, Johannes; Kirisgil, Melek; Fischer-Waldschmidt, Gloria; Wewetzer, Christoph; Lehmkuhl, Gerd; Resch, Franz (Psychopathology, 2016)
Descriptive diagnoses of nonsuicidal self-injury (NSSI) and suicide attempts (SAs) may detract from underlying dimensional borderline personality pathology (D-BPP). This study aimed to investigate D-BPP in adolescent inpatients with NSSI and SAs. A consecutive sample of 359 adolescent inpatients was assessed for current and past NSSI and life-time SAs. D-BPP and current mental health problems were measured using the Dimensional Assessment of Personality Pathology and the Strengths and Difficulties Questionnaire, respectively. D-BPP was significantly associated with both current (p < 0.001) and past NSSI (p = 0.025) and life-time SAs (p < 0.001) compared to their non-self-harming peers. Patients with current and past NSSI did not differ in terms of D-BPP or current mental health problems. A multivariate model did not show any additional influence of current mental health problems over and above D-BPP in predicting NSSI and SAs. It can be hypothesized that D-BPP underlies adolescent self-harm and may persist even after its termination, promoting a higher burden of mental health problems.
Gesehen am 06.05.2020